2022
DOI: 10.3389/fmicb.2022.955825
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fungal communities and nonvolatile flavor components in black Huangjiu formed using different inoculation fermentation methods

Abstract: Black Huangjiu (BH) is a traditional alcoholic beverage in China, which is very popular among people. The different methods (simultaneous inoculation, sequential inoculation), were applied to ferment BH in this study, which were investigated the changes in the composition of fungal communities and non-volatile flavor compounds (nVFCs) by high-throughput sequencing (HTS) and ultraperformance liquid chromatography–tandem mass spectrometer (UPLC MS/MS). The results showed that Rhizopus and Saccharomyces were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…In this study, lipids and lipid-like molecules (e.g., 3-hydroxytetradecanedioic acid and 2-monolinolenin) were the most common in high-quality plant samples. The majority of contributors to lipids and lipid-like molecules exhibited a significant positive correlation with Saccharomyces ( p < 0.05), a result that notably contrasts with the findings of Li et al. (2022) .…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In this study, lipids and lipid-like molecules (e.g., 3-hydroxytetradecanedioic acid and 2-monolinolenin) were the most common in high-quality plant samples. The majority of contributors to lipids and lipid-like molecules exhibited a significant positive correlation with Saccharomyces ( p < 0.05), a result that notably contrasts with the findings of Li et al. (2022) .…”
Section: Discussioncontrasting
confidence: 82%
“…(2023) demonstrated that lipids and lipid-like molecules are closely related to volatile metabolite formation. Li et al. (2022) revealed that black Huangjiu (a traditional alcoholic beverage) fermented by sequential inoculation with Saccharomyces had a taste that was stronger, sweeter, mellower, and softer.…”
Section: Discussionmentioning
confidence: 99%
“…Under the conditions of VIP > 1.0, p < .01, FC > 4 or FC < 0.25, Figures 4a–c were selected to compare the differentially changed chemical compositions (Li et al, 2022 ; Wang et al, 2021 ) in ACF and ACGB, ACF and ACL, ACL and ACGB, respectively. Meanwhile, 30 chemical components, including 10 flavonoids (1–10), 8 lipids (11–18), 5 amino acid and derivatives (19–23), 4 carboxylic acids and their derivatives (24–27), 2 saccharides (28 and 29), and 1 heterocyclic compound (30) were identified as differentially changed chemical compositions (VIP > 1.0, p < .01, FC > 4 or FC < 0.25) in these three coffee samples, and structures of these chemical compounds are shown in Figure 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Under the conditions of VIP > 1.0, p < .01, FC > 4 or FC < 0.25, Figures 4a-c were selected to compare the differentially changed chemical compositions (Li et al, 2022;Wang et al, 2021) The Thermo Scientific automatic selected reaction monitoring (AutoSRM) software was used to process product-ion scan with a range of different collision energies. A total of 25 volatile compounds were identified by GC-MS as shown in Table 1 and were marked in Figures 6a-c.…”
Section: Chemical Compositions Of the Coffee Samplesmentioning
confidence: 99%
“…Metabolites in the tea leaves of NF and BF were extracted and then analyzed using a liquid chromatography-tandem mass spectrometry (LC-MS/MS) based metabolomics approach, performed by Meiji Biomedical Technology Co., Ltd. (Shanghai, China). Metabolite identification was dependent on the MS/MS data annotated against an in-house database, or the matches of both retention times and MS data to some standard compounds [35]. Variable importance in projection (VIP) was an indicator used to evaluate the correlation between a metabolite and a sample classification, and variables with VIP > 1.0, p < 0.05 (Student's t test) and fold change (FC) > 2 or <0.5 were considered as differentially changed metabolites (DCMS) [36].…”
Section: Metabolomics Analysismentioning
confidence: 99%